Anthropometric indices as predictors of 10-year cardiovascular risk among Sub-Sahara Africans with type 2 diabetes - Azeez TA Arinola Esan; Ayobami Imole Yemitan; Olumayowa Opeyemi Oluwasanjo; Mayowa Babatunde (Journal of Cardiovascular Medicine and Cardiology - Peertechz Publications, 2021)
Background: Body mass index, waist circumference, waist-hip ratio and waist-height ratio are simple clinical tools for determining obesity. Type 2 diabetes mellitus is often associated with multiple cardiovascular risk factors and increased cardiovascular death. The study was aimed at determining the relationship between these anthropometric indices and 10-year cardiovascular risk among sub-saharan Africans with type 2 diabetes mellitus. Methods: It was a cross-sectional study involving 67 adults (with 50.7% females) managed for type 2 diabetes mellitus in a referral hospital in Nigeria. Ethical approval was obtained at the institution review board and the participants also gave written consent. Anthropometric indices were determined using standard protocols. Fasting lipid profile, fasting plasma glucose, glycated haemoglobin and plasma creatinine were assayed using standard laboratory techniques. Atherogenic index of plasma, estimated glomerular filtration rate and the WHO-ISH cardiovascular risk score were also determined. Data was analyzed with SPSS version 22. Pearson correlation coefficient, Students' t test, Chi square test, ROC curve analysis were performed as appropriate. Results: The mean age was 54.12±9.03 years. Obesity was found in 37.3%, 66.5%, 70.1% and 95.5% of the participants using BMI, WHR, WC and WHtR respectively. Intermediate/high cardiovascular risk was found in 38.2% and 24.2% of the males and females respectively. BMI and WC significantly correlated with blood pressure. There was no significant correlation between anthropometric indices and other cardiovascular risk factors studied. Using ROC curve analysis, BMI and WHtR had the highest AUC of 0.613 and 0.577 respectively. Conclusion: Among sub-sahara Africans with type 2 diabetes mellitus, there is a significant association between WC and BMI with the blood pressure. BMI and WHtR have the highest 10-year cardiovascular risk predictability among the anthropometric indices in this cohort of individuals. Larger and prospective studies are needed to validate these findings.